1996
DOI: 10.1002/(sici)1098-2825(1996)10:3<149::aid-jcla7>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salivary and seric IgG and IgA antipooled pigeon sera activities in patients with pigeon breeder's disease

Abstract: Pigeon breeder's disease (PBD) is an interstitial lung disease induced by exposure to pigeon antigens. Search of antipigeon antigen antibodies (APSA) in serum or bronchoalveolar lavage is generally used for auxiliary diagnostic purposes. However, APSA can be present in a number of exposed but asymptomatic individuals as well as in patients with other interstitial lung diseases who live in areas where keeping pigeons is a common domestic habit. In this study, saliva was evaluated as an alternative means to seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The quantitation of antibody response against avian antigens, as well as the analysis of specific isotypes and immunoglobulin subclasses have recently suggested that high antibody levels and certain isotypes of AA may be useful as predictive and specific markers for PBD (3)(4)(5). Indeed, high titers of IgG and IgA AA reactivity against pigeon serum were found to be significantly associated with PBD and symptomatic breeders compared with asymptomatic relatives, healthy volunteers, and even with idiopathic pulmonary fibrosis patients (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…The quantitation of antibody response against avian antigens, as well as the analysis of specific isotypes and immunoglobulin subclasses have recently suggested that high antibody levels and certain isotypes of AA may be useful as predictive and specific markers for PBD (3)(4)(5). Indeed, high titers of IgG and IgA AA reactivity against pigeon serum were found to be significantly associated with PBD and symptomatic breeders compared with asymptomatic relatives, healthy volunteers, and even with idiopathic pulmonary fibrosis patients (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have emphasized that no single immunological test may definitively distinguish between antigen exposure and pigeon breeder's disease. Besides, no pathognomonic laboratory features appear to separate the HP group from other pulmonary disorders [2–8].…”
Section: Discussionmentioning
confidence: 58%
“…Comparison of pigeon lung with other pulmonary disorders through AA tests has only been assessed in few reports [36]. Diagnostic evaluation of AA through ELISA revealed that the IgG levels in pigeon breeder's disease exceeded the values of other respiratory disorders different from HP [7, 36±38] and no signi®cant overlapping AA results have been described in HP and idiopathic pulmonary ®brosis [7,8]. In the present study, high values of IgG and IgA were useful to distinguish HP from IPF and RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Measurement of rate of clearance of 99mTc-DTPA can identify alterations in pulmonary integrity more subtle than those found with conventional pulmonary function tests, and may therefore be a useful test for detecting the earliest stages of the illness. 16 Elevated angiotensin-converting enzyme levels are also indicative of disease activity in these patients.…”
Section: Discussionmentioning
confidence: 99%